A simple and cost-effective detection of capsule origin source using FTIR-ATR - Mustafa, Radhiahtul Raehan; Hamdan, Mohammad Naqib; Rahman, Siti Nur Hadis A.; Yusoff, Ida Madiha; Amin, Nor Suhada; Abdullah, Qosrina (Journal of food science and technology, 2025)
The adulteration of food by undeclared ingredients is a major problem for both consumers and regulatory authorities. The increasing demand for halal pharmaceuticals emphasises the need for a robust technique to identify porcine-derived components in samples. Fourier transform infrared spectroscopy coupled with attenuated total reflectance (FTIR-ATR) has emerged as a rapid, non-destructive and cost-effective technique for the detection of porcelain-derived components. In this study, 13 gelatine capsule samples from different sources were analysed with FTIR-ATR to investigate the presence of porcine and non-porcine. The application of discriminant analysis to the FTIR-ATR data allowed successful differentiation between porcine and non-porcine components in the samples. The infrared spectra revealed prominent functional groups, such as the amino group and the carbonyl group, which are characteristic of gelatin. While the spectra of the samples showed striking similarities due to their common major component, subtle differences were observed in the specific ranges of 3600–3000 cm −1 and 1700–1000 cm −1 . This integrated approach of FTIR-ATR and discriminant analysis proved to be a robust and reliable method for authenticating capsule origin and a useful tool for tracing halal detection in capsule products.